MEKANISME PELAKSANAAN MODEL LONG-TERM CARE (LTC) PELAYANAN SOSIAL LANJUT USIA TERLANTAR DI KOTA KENDARI - Lutfiana Nur Azizah; Amin Tunda; Nada Kusuma; Ghery Safitra Fahrun; Muh. Rijal (Jurnal Neo Societal, 2025)
This study aims to analyze the implementation mechanism of the long-term care (LTC) model for neglected elderly in Kendari City. The main focus of this study is to identify the service process, as well as the level of public and stakeholder awareness regarding the importance of handling social problems of neglected elderly. Using a descriptive qualitative approach, this study used in-depth interview techniques, observation, and documentation studies on 10 informants. The results of the study indicate that long-term care for neglected elderly involves various social programs and services. First, social assistance programs, namely Non-Cash Food Assistance , Family Hope Program, and Indonesian Healthy Card Contribution Assistance have been implemented to support the welfare of the elderly. Second, this study also highlights the implementation of the elderly rehabilitation assistance program, which includes family-based, community-based, and shelter-based services. Third, home-based care services are implemented by providing health and social care support in rehabilitation centers. Fourth, the community care program, which involves the active participation of the local community, has been shown to have a positive impact on maintaining the welfare of neglected elderly. And then, family care is very important in providing emotional and health support, especially for the elderly who live with their families. The elderly care system in Kendari city has integrated various approaches, both from the government, community, and family sides. The programs outlined provide a strong foundation for ensuring the welfare of poor and neglected elderly.